Impact of COVID-19 on Endoscopy Training: Perspectives from a Global Survey of Program Directors and Endoscopy Trainers - Shivakumar Vignesh; Amna Subhan Butt; Mohamed Alboraie; Bruno Costa Martins; Alejandro Piscoya; Quang Trung Tran; Damien Tan Meng Yew; Shahriyar Ghazanfar; Pezhman Alavinejad; Edna Kamau; Ajay M Verma; Robin B Mendelsohn; et al. (Korean Society of Gastrointestinal Endoscopy, 2021)
Background/Aims The coronavirus disease of 2019 (COVID-19) pandemic has impacted the training of medical trainees internationally. The aim of this study was to assess the global impact of COVID-19 on endoscopy training from the perspective of endoscopy trainers and to identify strategies implemented to mitigate the impact on trainee education. Methods Teaching faculty of gastroenterology (GI) training programs globally were invited to complete a 36-question web-based survey to report the characteristics of their training programs and the impact of COVID-19 on various aspects of endoscopy training, including what factors decisions were based on. Results The survey response rate was 52.6% (305 out of 580 individuals); 92.8% reported a negative impact on endoscopy training, with suspension of elective procedures (77.1%) being the most detrimental factor. Geographic variations were noted, with European programs reporting the lowest percentage of trainee participation in procedures. A higher proportion of trainees in the Americas were allowed to continue performing procedures, and trainers from the Americas reported receiving the greatest support for endoscopy teaching. Conclusions This study demonstrated that the COVID-19 pandemic has had a significant negative impact on GI endoscopy training internationally, as reported by endoscopy trainers. Focus-optimizing endoscopy training and assessment of competencies are necessary to ensure adequate endoscopy training.